ACCOUNTING DISCLOSURE IN THE FINANCIAL ACCOUNTING SYSTEM AND ITS ROLE IN THE QUALITY OF THE MANAGEMENT DECISIONS OF THE IRAQ STOCK EXCHANGE (World Economics and Finance Bulletin, 2024)
By meeting the demands of financial markets and facilitating investors' ability to make informed financial decisions, the financial accounting system seeks to align accounting standards in Iraq with those found elsewhere. Like every other stock exchange in the world, the Iraqi stock market must offer accurate and dependable financial data, and the only way to achieve this is to impose regulations governing the openness and disclosure of listed institutions' financial data. Consequently, investors' To attain market efficiency, trust and transaction volume may be raised. According to the study's findings, the effectiveness of the stock exchange increased when accounting transparency and an accounting system that delivers appropriate and accurate financial information were used.
Keywords: Account Disclosure; Stock Exchange; Financial Statements; Management Decisions.